Paeoniflorin improves cardiac function and decreases adverse postinfarction left ventricular remodeling in a rat model of acute myocardial infarction - Chen H; Dong Y; He X; Li J; Wang J (Dove Medical Press, 2018)
Hengwen Chen,* Yan Dong,* Xuanhui He, Jun Li, Jie Wang Guang’anmen Hospital, China Academy of Chinese Medical Sciences, Beijing, China *These authors contributed equally to this work Background: Paeoniflorin (PF) is the active component of Paeonia lactiflora Pall. or Paeonia veitchii Lynch. This study was, therefore, aimed to evaluate the improvement and mechanism of the PF on ventricular remodeling in rats with acute myocardial infarction (AMI). Materials and methods: In this study, AMI model was established by ligating the anterior descending coronary artery in Wistar rats. After 4 weeks gavage of PF, the apparent signs and the left ventricle weight index of Wistar rats were observed. The left ventricular ejection fraction (LVEF) was evaluated by Doppler ultrasonography. Changes in cardiac morphology were observed by pathologic examination, and apoptosis was observed by the terminal deoxynucleotidyl transferase dUTP nick end labeling assay. In addition, enzyme-linked immunosorbent assay was used to detect the expression of tumor necrosis factor-α (TNF-α), interleukin-6 (IL-6) interleukin-10 (IL-10) and brain natriuretic peptide (BNP). Immunohistochemistry and Western blot method were applied to detect Caspase-3 and Caspase-9. Results: Compared with the model control, the survival conditions of rats in all treatment groups were generally improved after PF treatment. LVEF was significantly increased, and both left ventricular end-diastolic inner diameter and left ventricular end-systolic inner diameter were significantly reduced. Moreover, pathologic examination showed that the myocardium degeneration of the rats treated with PF was decreased, including neater arrangement, more complete myofilament, more uniform gap and less interstitial collagen fibers. Furthermore, the mitochondrial structure of cardiomyocytes was significantly improved. The ultrastructure was clear, and the arrangement of myofilament was more regular. Also, the expression of Caspase-3 and Caspase-9 was inhibited, and apoptosis was obviously reduced in the PF treatment groups. BNP, TNF-α and IL-6 were also decreased and IL-10 was increased in the treated rats. Conclusion: PF could significantly improve the LVEF of rats. It decreased adverse left ventricular remodeling after myocardial infarction in rat models. The potential mechanism could be that PF decreased and inhibited BNP, TNF-α and IL-6, increased IL-10 and further inhibited the expression of Caspase-3 and Caspase-9, thus promoting ventricular remodeling. Keywords: paeoniflorin, ventricular remodeling, myocardial infarction, Caspase-3, Caspase-9